(untitled) (Global Journal of Science Frontier Research, 2022)
Between August 2019 and October 2020 an ethnobotanical research was carried out to look at how the inhabitants of Nabiganj Upazila of Bangladesh s Habiganj district was noted The information regarding the ethnobotanical data was obtained by interviewing residents of different age groups most of them were in the 15 to 55 age range including medicinal herbalists and hakims The present paper reported that 68medicinal plants belonging to 41 families and 60 genera which have been proven to be helpful in the treatment of 78 diseases Out of these plant species 24 belonged to herbs 27 trees eight shrubs and nine climbers However other parts of medicinal plants including the stem bark latex leaf bud pulp petiole fruits and rhizome Seed root calyx and peduncle were also shown to be helpful For each species scientific name local name habit family ailments to be treated mode of treatment and part s used are provided Local residents of gathered data on medicinal plants including Nabiganj Upazila of Habiganj district The rural populace relies on these plants as a form of treatment for numerous illnesses including but not limited to anemia aphrodisiac jaundice smallpox leprosy antiseptic cough sores skin disease cancer piles diarrhea diuretic low blood presser dysentery headache diabetes asthma toothache purify blood sedative gonorrhea fever In this article we will discuss how plants may be utilized for medical purposes